Retrospective task for a non-stationary operator of heat conductivity - Panin, V.V.; Krivoshey, F.A.; Bogdan, Yu.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The limit case of a retrospective task of non-stationary heat conductivity (namely, the restoration of the initial distribution of temperatures) is considered. The need for it can arise at expert estimates of the thermal prehistory of an object, for example, an internal combustion engine. The regularization of the solution of a non-correct Volterra integral equation of the first kind for the initial distribution of temperatures by Laplace’s stochastic transformation in the square approximation reduces the first-kind equation to a second-kind equation, whose solution is unique and stable relative to the errors of initial data.